Treatment of fetal circular shunt with non‐steroidal anti‐inflammatory drugs. (6th June 2019) - Torigoe, T.; Mawad, W.; Seed, M.; Ryan, G.; Marini, D.; Golding, F.; VAN Mieghem, T.; Jaeggi, E.
ABSTRACT: A circular shunt (CS) is a life‐threatening condition involving massive shunting of systemic arterial blood via the ductus arteriosus to the left ventricle without traversing the lungs. In the prenatal setting, it occurs mainly in fetuses with severe forms of Ebstein's anomaly (EA) owing to unrestricted ductal flow and significant pulmonary and tricuspid regurgitation. We aimed to improve the fetal hemodynamics and chances of survival of affected fetuses by inducing ductal constriction using transplacental non‐steroidal anti‐inflammatory drugs (NSAIDs). Following initiation of treatment between 26 and 34 weeks' gestation, three (75%) of four fetuses with EA/CS responded with sustained ductal constriction and improved hemodynamic function, which allowed continuation of pregnancy for 3–7 weeks and elective delivery. All successfully treated cases underwent neonatal surgery immediately after birth to eliminate the CS and survived. This included two neonates that underwent single‐ventricle palliation surgery that required postoperative extracorporeal membrane oxygenation and hemofiltration for transient respiratory and renal failure. The one case that did not respond to treatment with NSAIDs was delivered prematurely for progressive fetal compromise and died shortly after birth. Transplacental treatment with NSAIDs represents a novel approach to controlling fetal CS, avoiding in‐utero death and prolonging the pregnancy to a more advanced gestational age, thereby potentially increasing the chances of neonatal survival. This treatment should be considered and initiated at an early stage of systemic steal to prevent brain injury due to hypoperfusion. Copyright © 2018 ISUOG. Published by John Wiley & Sons Ltd.